The Role of the Bestee Program in Empowering and Increasing the Sustainability of MSMEs for BTPN Syariah Customers at MMS Peterongan Through Assistance Regarding the Importance of Procuring Business Identity - Saputri, Nanda Vernia Adji; Oktafia, Renny (International Journal of Community Service (IJCS), 2025)
At this time, MSMEs play an important role in increasing economic growth in a region. Because the more MSMEs there are in a region, the higher the economic growth in that region will be from time to time. The aim of this service is to provide knowledge and understanding about the importance of providing business identities for MSME actors at MMS Peterongan which will increase income and make the businesses of these MSME actors known to many people. The method used is the ABCD (Assest Based Community Development) method with 5 (five) activity stages, namely discovery, dream, design, define, and destiny. This will be done by meeting each customer and providing assistance to 30 customers. This mentoring activity was carried out over 4 sessions over a period of 4 months at MMS Peterongan, Jombang, East Java.